Land Economy and Rural Studies Essentials : Proceedings of the Conference on Land Economy and Rural Studies Essentials (LEASECON 2021) /: Proceedings of the Conference on Land Economy and Rural Studies Essentials (LEASECON 2021). (2022) - Unknown
No abstract available